The Senses of Agency and Ownership in Patients With Borderline Personality Disorder - Möller, Tim Julian; Braun, Niclas; Thöne, Ann-Kathrin; Herrmann, Christoph S.; Philipsen, Alexandra (Frontiers in Psychiatry, 2020)
Patients with borderline personality disorder (BPD) not only experience a strong instability in their affect and interpersonal relations, but also disturbances in their self-experience, including dissociation and body-alienation symptoms. It is not yet understood whether an altered sense of ownership (SoO) or sense of agency (SoA) may contribute to these disturbances. One recent hypothesis is that patients with BPD have a reduced sense of self and are therefore more likely to misattribute external objects or actions to their own self than healthy persons. The present study followed up this hypothesis by investigating whether BPD patients have a more flexible body representation than healthy participants. More specifically, the active rubber hand illusion (aRHI) was applied to 21 patients with BPD and the same number of healthy participants. Using established subjective, electrodermal, and behavioral measures, the participants’ SoO and SoA were assessed during the aRHI. The findings show self-reported evidence for higher SoO under anatomical hand congruency as compared to anatomical incongruency, but no evidence for group differences between BPD patients and healthy participants. This finding is inconsistent with previous findings of an enhanced SoO-related body plasticity in BPD patients. Regarding SoA, the findings show self-report evidence of higher SoA in BPD patients versus healthy participants, although this group difference was not evident in the implicit SoA measure (intentional binding). In summary, the present study only reveals partial evidence for a higher body plasticity in BPD patients. Instead, the observed variability in results appears better explainable by some generally elevated perceptual suggestibility of BPD individuals.